Design of A Decision Support System for Employee Recruitment Using the Simple Additive Weighting (SAW) Method Based on Java - Ananda, Shelly Tria; Susano, Adhi; Pinahayu, Ek Ajeng Rahmi (Yayasan Meira Visi Persada, 2024)
This system is designed to create a Decision Support System (DSS) that effectively and efficiently aids in the employee selection and recruitment process at PT. XYZ using the Simple Additive Weighting (SAW) method, implemented in Java. The system supports the company in selecting and hiring employees based on specific criteria. The research involves collecting data through surveys and interviews with relevant stakeholders. The collected data is analyzed using the SAW method, which is chosen for its ability to deliver accurate and easy- to-understand decision-making outcomes by aggregating the weights of each normalized criterion. The system is developed using Java NetBeans, which simplifies the design process of this decision support system. The research findings indicate that the system is capable of providing effective and accurate recommendations for employee selection at PT. XYZ. It evaluates candidates based on relevant criteria, such as skills, experience, and other qualifications aligned with the company's requirements. Additionally, the system organizes and securely stores data related to these criteria in its database.